Assessing the Impact of Cognitive Training on Children with ADHD: A Qualitative Analysis - Pradhan, Sasanka Sekhar; Neha Negi; Sumita Harish Sugand (Gayaku Publisher, 2024)
Cognitive training has become one of the most promising interventions for children diagnosed with Hyperactive Disorder, commonly known as ADHD, or attention deficit hyperactivity disorder. It is a qualitative study seeking to uncover the advantages of cognitive training towards children suffering from hyperactivity disorder. The study focuses on the perspectives and experiences of the parents, teachers, and medical professionals who look after and grow these kids. Through focus groups and semi-structured interviews, information about alterations in academic performance, attention span, and behavioural regulation is obtained. Findings indicated that there is a possibility that cognitive training may be an effective tool in improving the executive functioning of disruptive children with hyperactive disorder, and results seem to vary according to the characteristics of the child and approach of the training involved. Some recommendations for educators and therapists are provided as well as ideas for future research.